2001
DOI: 10.1053/eujp.2001.0274
|View full text |Cite
|
Sign up to set email alerts
|

Special aspects of cancer pain management in a Chinese general hospital

Abstract: China is still faced with a challenge in cancer pain management. The purposes of this study are to assess the current status of cancer pain management, and physicians' attitudes in China towards cancer pain management. The survey was done in a Chinese general hospital; 427 physicians and 387 cancer pain patients participated. The survey consisted of questionnaires to evaluate cancer pain management and physicians' knowledge of, and attitudes towards, cancer pain management. A total of 43% of patients with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…As expected, professional-related barriers included insufficient knowledge and poor evaluation of pain, lack of adherence to pain management guidelines, too much concern about addiction, and a low priority given to cancer pain control in treatment. Above all, several studies have reported that medical staff frequently have erroneous knowledge and simply do not pay attention to pain assessment [7,8,9,10]. Other factors such as reluctance to prescribe opioids, lack of access to opioids, and excessive regulation to prevent over-prescribing of opioids were demonstrated less frequently.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, professional-related barriers included insufficient knowledge and poor evaluation of pain, lack of adherence to pain management guidelines, too much concern about addiction, and a low priority given to cancer pain control in treatment. Above all, several studies have reported that medical staff frequently have erroneous knowledge and simply do not pay attention to pain assessment [7,8,9,10]. Other factors such as reluctance to prescribe opioids, lack of access to opioids, and excessive regulation to prevent over-prescribing of opioids were demonstrated less frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Second, due to a lack of personalized pain control knowledge, some medical staff could not appropriately manage pain. Third, some local hospital policies for regulating narcotics might restrict the use of opioid analgesics[10], [14]–[18].…”
mentioning
confidence: 99%
“…Because of pharmacological characteristic of transdermal fentanyl, it was mild for nausea, vomiting, constipation, and the risk of abuse was obviously decreased. There was no report about abusing and addiction (psychological dependence) for transdermal fentanyl [7] . The patch is used to cancer patients with chronic pain, especially to patients with difficulty swallowing, gastrointestinal dysfunction and outpatients with advance cancer.…”
Section: Discussionmentioning
confidence: 99%